Clinical and biochemical outcomes of laparoscopic adrenalectomy in patients with Conn’s syndrome: experience from a tertiary referral center in Mexico - Saavedra-Flores, Denisse R.; Escobar-González, Alejandra; García-Félix, Itzel G.; Gomez-Arenas, Samuel R. (International Surgery Journal, 2026)
Unilateral primary aldosteronism, also known as Conn’s syndrome, is a potentially curable cause of secondary arterial hypertension. Laparoscopic adrenalectomy represents the treatment of choice in selected patients, there are few national reports regarding its clinical and perioperative outcomes. A retrospective, observational, single-center case series was conducted on patients diagnosed with unilateral primary aldosteronism who underwent laparoscopic adrenalectomy at the Department of General Surgery of the High Specialty Medical Unit No. 25, Northeast National Medical Center, Mexican Social Security Institute (IMSS), Monterrey, Nuevo León, Mexico, between January 2020 and December 2024. The mean age was 46.3 years, and 58.3% of the patients were male. Preoperative hypokalemia was present in 91.7% of cases, and the mean number of antihypertensive medications was 3. Postoperatively, complete success was observed in 75% and partial success in 25%, with no cases of biochemical or clinical persistence. Resolution of hypokalemia was documented in 100% of patients, along with a significant decrease in serum aldosterone levels and the aldosterone-renin ratio, as well as a substantial reduction in antihypertensive requirements. There were no conversions to open surgery or perioperative complications, with a mean hospital stay of 24 hours. The predominant histopathological diagnosis was adrenal adenoma 91.7%. In this cases series study, laparoscopic adrenalectomy demonstrated a high rate of clinical and biochemical success, an excellent perioperative safety profile, and adequate resolution of the metabolic alterations associated with Conn’s syndrome. These findings support its role as the treatment of choice for patients with unilateral primary aldosteronism.